Clinicodemographic, radiological, and immunological profiles of allergic bronchopulmonary aspergillosis in a tertiary care institute in Eastern India - Shankar, Manish; Choubey, Satyadeo; Ejazi, Arshad (International Journal of Research in Medical Sciences, 2022)
Background: Allergic bronchopulmonary aspergillosis (ABPA) is a type of hypersensitivity reaction to mold Aspergillus fumigatus, especially common in patients with bronchial asthma. However, systemic data regarding the clinicodemographic, radiological, and immunological profiles of patients is sparse, particularly from the eastern India. Methods: This is a prospective observational study done over a year, from January 2021 to December 2021, in patients visiting the pulmonary medicine outpatient department (OPD) with symptoms similar to ABPA. Following the clinical examination, routine blood investigations, serum total immunoglobulin E (IgE) test, Aspergillus-specific IgE test, spirometry, and chest radiology (chest X-ray/high resolution CT scan) were done. ABPA was diagnosed using the 2013 ISHAM-ABPA working group criteria. Data were analyzed using statistical package for the social sciences (SPSS) software version 2021 against different categories of eosinophil count. Results: A total of 99 patients, 74 male and 25 female, were diagnosed with ABPA. The mean age±standard deviation (SD) was 37.66±15.411. Most of the patients (93) were asthmatic. Chest radiology was normal in 52.5% of the cases. The absolute eosinophil count (mean±SD) was 3963.61±5333.363. The mean±SD serum IgE and Aspergillus-specific IgE levels were 8061.07±8374.274 and 7.5826±12.693, respectively. Conclusions: There was no significant association between lung function abnormalities and eosinophil count. Serology variant (ABPA-S) was the most common finding among ABPA patients. A high eosinophil count was associated with a high incidence of bronchiectasis and hyper attenuated mucus (HAM), although the severity of bronchiectasis was not directly related to a higher peripheral eosinophil count. There may be some correlation between the peripheral eosinophil count and the total IgE but not between the peripheral eosinophil count and the Aspergillus-specific IgE.